The intercultural experiences of Chinese international students in the UK - Lin Zheng; Will Baker (Insights into Language, Culture and Communication, 2022)
This paper aims to investigate a group of Chinese students’ intercultural encounters studying in two articulation programmes in one British university and analyses the barriers that seem to exist between them, home and other international students. This research is qualitative in nature. Thematic analysis of sixteen Chinese students’ interviews and reflective narratives were adopted. A core finding is that the power of the ‘Chinese circle’ provides this group with a comfortable zone but also presents a barrier to engaging in intercultural communication and developing more intercultural identities. Contributing factors to this pull of the Chinese circle include changing attitudes to English and Chinese language, negative intercultural experiences, and a lack of awareness of intercultural identity.  It is suggested that universities should diversify their international recruitment, enhance intercultural education and training provided for all international students before and during their studies abroad.